2020
DOI: 10.21273/hortsci15111-20
|View full text |Cite
|
Sign up to set email alerts
|

‘Ray Ruby’ Grapefruit Affected by Huanglongbing I. Planting Density and Soil Nutrient Management

Abstract: Huanglongbing (HLB), or citrus greening disease, affects practically all fruit-bearing trees in commercial citrus orchards in Florida with no cure identified yet. High-density plantings and enhanced nutritional programs such as application of controlled-release fertilizer (CRF) with higher micronutrient levels can mitigate disease symptoms and extend the tree life span of sweet oranges (Citrus sinensis). The objective of this study was to evaluate the effects of tree planting density and application of CRF ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The high planting density used in this study (1111 trees/ha) might have masked the effects of plant nutrition on vegetative growth variables, as higher densities promote higher competition among nutrients, water, space, and light, which may affect vegetative growth (Weil and Brady, 2017). This is supported by the findings of Phuyal et al (2020aPhuyal et al ( , 2020b who observed lower canopy volume and trunk diameter with a high planting density (975 trees/ha) when compared with lower planting densities of (300 and 440 trees/ha) of 'Ray Ruby' grapefruit on Kuharske citrange. However, they found greater fruit yield per hectare with the highest planting density, with no significant yield difference among fertilizer treatments.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The high planting density used in this study (1111 trees/ha) might have masked the effects of plant nutrition on vegetative growth variables, as higher densities promote higher competition among nutrients, water, space, and light, which may affect vegetative growth (Weil and Brady, 2017). This is supported by the findings of Phuyal et al (2020aPhuyal et al ( , 2020b who observed lower canopy volume and trunk diameter with a high planting density (975 trees/ha) when compared with lower planting densities of (300 and 440 trees/ha) of 'Ray Ruby' grapefruit on Kuharske citrange. However, they found greater fruit yield per hectare with the highest planting density, with no significant yield difference among fertilizer treatments.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, Atta (2019) did find that the 280 kgÁha À1 N rate significantly increased canopy volume of 'Hamlin' on Swingle rootstock, indicating that scion and rootstock selections can affect fertilization experiments of HLB-affected trees. Similarly, Phuyal et al (2020aPhuyal et al ( , 2020b found that higher N, Mg, and micronutrient inputs increased canopy volume of 'Ray Ruby' grapefruit on Kuharske citrange, although this occurred at the expense of fruit yield.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, yield efficiency (yield per unit canopy volume) is a more suitable variable for determining productivity of a mature orchard. In two recent studies of 'Ray Ruby' grapefruit, high-density planting resulted in increased yield per hectare, increased fruit TSS contents, and decreased canopy volume (Phuyal et al, 2020). This demonstrates that the use of high-yield efficient rootstocks and optimized planting density can increase productivity and minimize cost per unit production.…”
Section: Rootstockmentioning
confidence: 94%
“…Frequent application of small doses of fertilizers (in leaves or roots) enabling regular supply of nutrients are more effective in reducing potential nutrient leaching. Fertigation and controlled-release fertilizers are also effective nutrient delivery methods (Phuyal et al, 2020;Morgan et al, 2016).…”
Section: Irrigation Nutrition Management and Hormonesmentioning
confidence: 99%